Understanding Motor Skills in Children with Dyspraxia, ADHD, Autism, and other Learning Disabilities : A Guide to Improving Coordination - Kurtz, Lisa A. (Jessica Kingsley Pubs, 2008)
159 p.; ill.; 23 cm.